Biomechanical and bioactivity concepts of polyetheretherketone composites for use in orthopedic implants : a review - Abdullah, Mohamed Ruslan (Wiley Periodicals, 2015)
The use of Polyetheretherketone (PEEK) composites in the trauma plating system, total replacement implants, and tissue scaffolds has found great interest among researchers. In recent years (2008 afterward), this type of composites has been examined for suitability as substitute material over stainless steel, titanium alloys, ultra high molecular weight polyethylene (UHMWPE), or even biodegradable materials in orthopaedic implant applications. Biomechanical and bioactivity concepts were contemplated for development of PEEK orthopaedic implants and a few primary clinical studies reported the clinical outcomes of PEEK-based orthopaedic implants. This study aims to review and discuss the recent concepts and contribute further concepts in terms of biomechanical and bioactivity challenges for development of PEEK and PEEK composites in orthopaedic implants. This article is protected by copyright.